(untitled) (Annals of the University of Bucharest. Political Science Series, 2025)
This article explores press coverage of sport-related violence in the Czech Republic by applying Stuart Hall’s analytical framework to articles published in selected newspapers between 1998 and 2017. Covering a gap in the current scholarship, this case study shows that in the Czech Republic there are similar trends to the ones present in other European countries when it comes to media coverage of sport-related violence. However, the typical simplifications and exaggerations associated to the topic are present only in a minor part of the analysed sample and even tabloid press articles report rather neutrally on the matter. There is also a marked difference in how the newspapers report on football- and ice hockey-related violence, with the former largely explained by football supporters’ characteristics and the latter more readily interpreted as directly influenced by the game. The scarce calls for action and reactions from politicians, as well as the fact that police and game authorities are usually those who seem to frame the topic support the thesis that sport-related violence is more often politicised by actors that deal with it as part of their everyday duties, while politicians only exploit it under certain socio-political circumstances.